(untitled) (Research, Society and Development, 2020)
To evaluate the periodic deworming programme (PDP) against soil-transmitted helminth infection and estimate the cost-benefit of this action in a Northeastern Brazilian State. An observational descriptive study was peformed by two branches: an epidemiological analysis of parasitological stool tests positivity in the 7 health micro-regions of Sergipe State, from January to June 2019, and a cost-benefitial analysis through comparison between estimated costs of PDP and conventional diagnose and treatment method from 2014 to 2018. From the 1110 parasitological stool tests evaluated, 317 were positive: 20 (1.8 %) for helminths and 307 (26.7%) for protozoan parasites. Among positive tests, 61 (19.2%) were in PDP age target group (5-14 years). An annual average of 255,283 Albendazole tablets (400mg, single dose) were distributed with an annual average coverage rate of 84.2%. To support the programme, approximately R 281,859.25 (US 89,775.67) were transferred per year to the state of Sergipe. PDP estimated cost-effectiveness was R 1.10 (US 0.34) per event prevented and generated a cost-minimization of approximately R 335.617,60 (US124,568.00) when compared to the conventional diagnose and treat method. The positive rates of soil-transmitted helminth infection in parasitological tests in Sergipe were low and the recommendation for PDP seems to be currently inadequate. Most positive tests were for commensal protozoa species. PDP estimated cost is lower than conventional diagnose and treatment method. Protozoa infections prevention policies should be evaluated as they are the major parasitic infection in our community after PDP.